2018
DOI: 10.1111/jmcb.12555
|View full text |Cite
|
Sign up to set email alerts
|

Propagation Mechanisms for Government Spending Shocks: A Bayesian Comparison

Abstract: The inability of a simple real business cycle model to predict a rise in consumption in response to increased government expenditures, observed in many empirical studies, has stimulated the development of alternative theories of government spending shocks. Using the Bayesian approach, we evaluate the quantitative performance of five extant models, and find that neither of the considered transmission mechanisms for government spending helps improve the fit of the baseline model. Moreover, we find that consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 68 publications
(185 reference statements)
3
13
0
1
Order By: Relevance
“…Similarly, Coenen et al (2012) suggested that we can observe a crowding-in effect on private consumption when the model is based on two assumptions: there is complementarity between private consumption and public spending, and government consumption is included in the utility function in an inseparable manner. This is consistent with models estimated by Kormilitsina and Zubairy (2016), who were not able to find a crowding-in effect of public spending on private consumption.…”
Section: Literature Reviewsupporting
confidence: 90%
“…Similarly, Coenen et al (2012) suggested that we can observe a crowding-in effect on private consumption when the model is based on two assumptions: there is complementarity between private consumption and public spending, and government consumption is included in the utility function in an inseparable manner. This is consistent with models estimated by Kormilitsina and Zubairy (2016), who were not able to find a crowding-in effect of public spending on private consumption.…”
Section: Literature Reviewsupporting
confidence: 90%
“…Thus, while the distribution of news shocks does make the average Ramey multiplier   smaller (closer to its  + value), this effect is not enough to compensate the fact that  +    + and  −    −  As a result, we find      in Table 1 and 2 (as in Ramey and Zubairy, 2016). 35 The discussion of New-Keynesian models with government spending is not meant to be exhaustive, and other mechanisms can generate a multiplier above 1 (see e.g., Kormilitsina and Zubairy, 2016). The goal of the discussion is to highlight simple channels that can lead to an asymmetric multiplier.…”
Section: Theoretical Discussionmentioning
confidence: 87%
“…27 Such shocks include (but not exclusively) shocks to government spending and thus contain information on the size of the government spending multiplier.…”
Section: Jorda and Taylor (2016)mentioning
confidence: 99%
“…The effect of an increase in government spending is a central issue in macroeconomics. In this regard, different macroeconomic models have achieved contrasting conclusions about the response of private consumption to government spending shocks (see, among others: Baxter and King 1993;Ambler and Paquet 1996;Linnemann and Schabert 2006;Forni et al 2009;Leeper et al 2010;Enders et al 2011;Coenen et al 2012;Corsetti et al 2012;Kormilitsina and Zubairy 2018;Beidas-Strom and Lorusso 2019).…”
Section: Introductionmentioning
confidence: 99%